Formulation of Scrub Preparations With Variations in the Concentration of Seagrass Leaf Ethanol Extract (Enhalus acoroides) - Inayah, Somatul; Prabandari, Rani; Sunarti, Sunarti; Nawangsari, Desy (International Journal of Education, Information Technology, and Others, 2024)
Seagrass leaves (Enhalus acoroides) are known to contain antioxidants that can protect the skin from free radicals and keep the skin's pH stable. Group compounds found in seagrass leaf components are fernolics, tannins, flavonoids, and glycosides. To facilitate the application of seagrass leaf extract, it is necessary to formulate one of them, namely scrub preparations. Seagrass leaf ethanol extract formulation uses variations in concentrations of F1 20%, F2 30% and F3 40%. The purpose of the study was to determine physical properties tests, irritation tests and moisture tests on seagrass leaf ethanol extract scrub preparations. Seagrass leaf extract was extracted by remaceration method using 70% ethanol then formulated into scrub preparations. Scrub is a liquid or semisolid preparation in the form of an emulsion. The results of the physical properties test of scrub preparations showed semisolid preparations of green to dark green color, had a characteristic seagrass odor and were homogeneous because they did not show the presence of coarse grains. F1 viscosity results 39,260, F2 results 39,278, F3 results 39,385, dispersion tests obtained F1 7.93, F2 results 8 and F3 results 7.73, then F1 adhesion test results 5.63, F2 results 5.75, F3 results 7.14 and F1 pH test results of 5.7, F2 results 5.6 and F3 5.6. In the irritation test results, the three formulas showed no irritation and the moisture test of the three formulas was less moist. It can be concluded that the results of the physical properties test of viscosity, pH, adhesion and dispersion tests are in accordance with the range required, the irritation test in the three formulas does not occur irritation and in the moisture test the results obtained are moist.